Precision measurement of the Ξ−b baryon lifetime - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Physical review, 2024)
A sample of 𝑝⁢𝑝 collision data, corresponding to an integrated luminosity of 5.5 fb−1 and collected by the LHCb experiment during LHC Run 2, is used to measure the ratio of the lifetime of the Ξ−𝑏 baryon to that of the Λ0𝑏 baryon, 𝑟𝜏 ≡𝜏Ξ−𝑏/𝜏Λ0𝑏. The value 𝑟𝜏 =1.076 ±0.013 ±0.006 is obtained, where the first uncertainty is statistical and the second systematic. This value is averaged with the corresponding value from Run 1 to obtain 𝑟Run 1,2𝜏 =1.078 ±0.012 ±0.007. Multiplying by the world-average value of the Λ0𝑏 lifetime yields 𝜏Run 1,2Ξ−𝑏=1.578±0.018±0.010±0.011 ps, where the uncertainties are statistical, systematic, and due to the limited knowledge of the Λ0𝑏 lifetime. This measurement improves the precision of the current world average of the Ξ−𝑏 lifetime by about a factor of 2, and is in good agreement with the most recent theoretical predictions.
Im Titel ist das Zeichen "-" hochgestellt und der Buchstabe "b" ist tiefgestellt
The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, F.C. Glaser, P.A. Günther, X. Han, S. Hausmann-Menzemer, P. Herrero Gascon, J. Hu, J. Kubat, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, S.R. Roy, M. Ruiz Diaz, M. Schmelling, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov und weitere 1057
Gesehen am 14.07.2025